Gaya Hidup Hedonisme Mahasiswa UIN Suska Riau Prespektif Gender - Irma Fitriani; Nurul Adila; Alsi Ratu Balqis; Muhammad Al-Habib; Sukma Erni (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2024)
A hedonistic lifestyle, which reflects the behavior of seeking unlimited pleasure, is increasingly common among UIN Suska Riau students. This phenomenon indicates a change in values among the younger generation which places more emphasis on personal satisfaction and instant pleasure. Students, as part of a generation that is in transition to adulthood, are vulnerable to the influence of a hedonistic lifestyle. The increasing trend of hedonism among students can influence various aspects of life, including academic, social and emotional. At UIN Suska Riau, the impact of a hedonistic lifestyle may differ based on gender, reflected in the social roles and expectations associated with men and women. This difference can influence the response and achievement of a hedonistic lifestyle between male and female students. This research is important because there has been no comprehensive study on the hedonistic lifestyle among UIN Suska Riau students from a gender perspective. Most of the literature focuses on the general impact of hedonism without breaking down the analysis by gender. However, a deeper understanding of gender differences in this context can provide more comprehensive insights and help in designing appropriate interventions. By investigating differences in perceptions and practices of hedonism between male and female students, this research seeks to provide a broader overview of this phenomenon. Incorporating gender analysis in research on hedonistic lifestyles is expected to provide a deeper understanding and become a guide for the development of targeted intervention programs. This research used a phenomenological method with a descriptive approach, involving 30 UIN Suska Riau students through questionnaires, participatory observation and documentation analysis. Data were analyzed using content analysis to identify patterns, themes and meanings that emerged from respondents' narratives and observations.